2019
DOI: 10.1093/mnras/stz311
|View full text |Cite
|
Sign up to set email alerts
|

On the Oosterhoff dichotomy in the Galactic bulge: I. spatial distribution

Abstract: We present a study of the Oosterhoff (Oo) dichotomy in the Galactic bulge using 8 141 fundamental mode RR Lyrae stars. We used public photometric data from the Optical Gravitational Lensing Experiment (OGLE) and the Vista Variables in the Vía Láctea survey (VVV). We carefully selected fundamental mode stars without modulation and without association with any globular cluster located toward the Galactic bulge. Subsequently, we identified and separated the Oosterhoff groups I and II on the basis of their period-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 71 publications
4
35
1
Order By: Relevance
“…15 outlines the boundary between Oosterhoff type I (hereafter OoI) and Oosterhoff type II (hereafter OoII) variables. This line is based on third-degree polynomial relation from table 2 in Prudil et al (2019) and a shift in the pulsation period by 0.045 day from Miceli et al (2008). We note, that the boundary between OoI and II globular clusters shifts with metallicity and the transformation of V amplitudes into I band can affect the association of individual modulated stars in the Oosterhoff groups.…”
Section: The Blazhko Stars With Respect To the Bailey's Diagrammentioning
confidence: 88%
See 3 more Smart Citations
“…15 outlines the boundary between Oosterhoff type I (hereafter OoI) and Oosterhoff type II (hereafter OoII) variables. This line is based on third-degree polynomial relation from table 2 in Prudil et al (2019) and a shift in the pulsation period by 0.045 day from Miceli et al (2008). We note, that the boundary between OoI and II globular clusters shifts with metallicity and the transformation of V amplitudes into I band can affect the association of individual modulated stars in the Oosterhoff groups.…”
Section: The Blazhko Stars With Respect To the Bailey's Diagrammentioning
confidence: 88%
“…The fact that majority of modulated stars is located in the OoI group also tells a little bit about their physical properties in comparison with OoII stars. For example, the difference in masses between both Oosterhoff groups has been suggested in the past (Catelan 1992;Cacciari & Bruzzi 1993;Sandage 2006;Prudil et al 2019), where the masses of OoII stars should be equal or larger in comparison with the OoI group. More importantly, the OoI variables lie close to the blue-edge of the instability strip and on are on average intrinsically hotter by several hundred Kelvins (Prudil et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pericenter peak RR Lyrae stars fall into the regions typical for the fundamental mode RR Lyrae stars with short pulsation periods and asymmetric light curves. In the period-amplitude diagram they can be all clearly associated with the Oosterhoff type I group (Oosterhoff 1939) identified in the Galactic bulge (Prudil et al 2019a). Moreover, a large fraction of the pericenter-peak RR Lyrae stars occupy the regions of high-amplitude short-period (from hereon referred to as HASP, Fiorentino et al 2015) RR Lyrae stars, which are found mainly in the most metal-rich systems (cf.…”
Section: Possibility Of Misclassificationmentioning
confidence: 89%